Relationship of plasma glucose to performance and carcass traits in finishing cattle - H.J. LaBrune; D.J. Bindel; C.C. Coetzer; C.A. Löest; R.D. Hunter; James J. Higgins; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2000)
Blood glucose levels of finishing cattle were measured between 3 and 30 days prior to slaughter and compared to performance and carcass traits. In trial 1, blood samples were obtained from 318 heifers at 2 hours postfeeding at 30 days before slaughter. Plasma glucose levels were correlated positively with fat thickness (P<.01) and kidney, pelvic, and heart fat (P<.02). Trial 2 utilized 72 steers from which blood was collected at 15 hours postfeeding at 3 days before slaughter. Blood glucose was correlated positively with average daily gain (P<.01); dry matter intake (P<.01); hot carcass weight (P<.01); ribeye area (P<.01); fat thickness (P<.06); and kidney, pelvic, and heart fat (P<.01). A third trial was conducted with 77 individually fed steers to determine if blood glucose levels could be used to predict finishing performance and carcass traits. Contrary to trials 1 and 2, plasma glucose did not reflect performance or carcass traits except marbling score (P<.03).
Keywords: Cattlemen' s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Glucose; Finishing cattle